Perioperative Morbidity and Complications in Patients With an Established Ileostomy Undergoing Major Abdominal Surgery: A Retrospective Study - Uribe, Alberto A.; Weaver, Tristan E.; Echeverria-Villalobos, Marco; Periel, Luis; Shi, Haixia; Fiorda-Diaz, Juan; Gonzalez-Zacarias, Alicia; Abdel-Rasoul, Mahmoud; Li, Lin (Frontiers in Surgery, 2021)
Background: Recently formed ileostomies may produce an average of 1,200 mL of watery stool per day, while an established ileostomy output varies between 600-800 mL per day. The reported incidence of renal impartment in patients with ileostomy is 0.8% - 20%, which could be caused by dehydration (up to 50%) or high output stoma (up to 40%). There is a lack of evidence if an ileostomy could influence perioperative fluid management and/or surgical outcomes. Methods: Subjects aged ≥18 years old with an established ileostomy scheduled to undergo an elective non-ileostomy related major abdominal surgery under general anesthesia lasting more than 2 hours and requiring hospitalization were included in the study. The primary outcome was to assess the incidence of perioperative complications within 30 days after surgery. Results: A total of 552 potential subjects who underwent non-ileostomy related abdominal surgery were screened, but only 12 were included in the statistical analysis. In our study cohort, 66.7% of subjects were males and the median age was 56 years old ([IQR] 48-59). The median time from creation of ileostomy to the qualifying surgery was 17.7 months (IQR: 8.3, 32.6). The most prevalent comorbidities in the study group were psychiatric disorders (58.3%), hypertension (50%), and cardiovascular disease (41.7%). The most predominant surgical approach was open (8 [67%]). The median surgical and anesthesia length was 3.4 hours (IQR: 2.5, 5.7) and 4 hours (IQR: 3, 6.5), respectively. The median PACU stay was 2 hours (IQR: 0.9, 3.1), while the median length of hospital stay (LOS) was 5.6 days (IQR: 4.1, 10.6). The overall incidence of postoperative complications was 50% (n=6). Two subjects (16.7%) had a moderate surgical wound infection, and two subjects (16.7%) experienced a mild surgical wound infection. In addition, one subject (7.6%) developed a major postoperative complication with atrial fibrillation in conjunction with moderate hemorrhage. Conclusions: Our findings suggest that the presence of a well-established ileostomy might not represent a relevant risk factor for significant perioperative complications related to fluid management or hospital readmission. However, the presence of the peristomal skin complications could trigger a higher incidence of surgical wound infections.